PREFACE FOR THE SPECIAL ISSUE ON LOGISTICS AND MARITIME SYSTEMS - Moon, Ilkyeong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The first International Conference on Logistics and Maritime Systems (LOGMS) was held in Busan, Korea, from September 15 to 17, 2010. The conference was launched by integrating the International Conference on Intelligent Logistics System (IILS) and the International Symposium on Maritime Logistics and Supply Chain Management (MLOG). With the increase in economic activities and the globalization of international trade, logistics has become a key factor in global companies. As mentioned by Professor Kap Hwan Kim, the chair of organizing committee, the worldwide economic situation has become more interconnected, uncertain, and dynamic; the traditional approaches to logistics and maritime management are no longer sufficient. The conference provided an opportunity for the researchers to discuss and exchange information, knowledge, ideas, and technologies regarding the development of logistics and maritime systems. About 200 participants from 17 countries actively participated in the conference. There were 31 technical sessions with 112 presentations along with 4 keynote speeches. Various topics were discussed in the technical sessions, such as seaport and transportation, maritime, shipping, supply chain management, inventory and production, simulation, business process management for logistics, which are closely related to the logistics and maritime system. Thirty two papers from the 112 papers were invited by the Program Committee for this special issue. Finally, 18 papers were accepted after a thorough review process. Several papers were related to empty container repositioning. Long et al. considered the planning for maritime empty container repositioning using a case study that involved 49 ports and 44 services. Yun et al. addressed inland container transportation in which the containers are transported by trucks and trains with time windows. Some papers studied the operations of a container terminal, such as Sung et al., Choi et al., and Daduna. Other papers were related to inventory management, logistics process management, and the maintenance system; thus, this issue covers a broad spectrum on logistics and maritime systems. For the success of this issue, I would like to express our deep appreciation to the reviewers who provided thorough reviews to the papers. Moreover, I would like to thank Professor Mital and Professor Pennathur for their support in bringing out this issue. I am quite sure that this special issue will provide important references for logistics and maritime studies. Professor ILKYEONG MOON, Guest Editor Department of Industrial Engineering, Seoul National University Seoul, KOREA Email: ikmoon@snu.ac.kr